Colorimetric and electrochemical analysis of DNAzyme-LAMP amplicons for the detection of Escherichia coli in food matrices - Alaa H. Sewid; Haley C. Dylewski; Joseph H. Ramos; Bailey M. Morgan; Benti D. Gelalcha; Doris H. D’Souza; Jie Jayne Wu; Oudessa Kerro Dego; Shigetoshi Eda (Scientific Reports)
Abstract Foodborne bacteria like Escherichia coli threaten global food security, necessitating affordable, on-site detection methods, especially in resource-limited settings. This study optimized loop-mediated isothermal amplification (LAMP) integrated with peroxidase-mimicking G-quadruplex DNA structures (DNAzyme), termed DNAzyme-LAMP which was designed to incorporate two different catalytic DNAzymes per amplification unit, enabling colorimetric detection of E. coli in leafy vegetables and milk samples. Additionally, we introduce a novel electrochemical method that enhances analytical sensitivity. The optimized DNAzyme-LAMP achieved a detection limit below 6.3 CFU per reaction or 0.1 aM gene copies. This system lays the groundwork for the development of on-site biosensors and can be adapted for detecting other foodborne pathogens.